2005
DOI: 10.1111/j.1745-4514.2005.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ionic Strength in Biochemical Properties of Soluble Fish Proteins Isolated From Cryoprotected Pacific Whiting Mince

Abstract: Biochemical characteristics of Pacific whiting muscle proteins extracted at acidic, neutral and alkaline conditions were investigated as affected by various ionic strength levels. The protein solubility at pH 4 declined, as NaCl was added up to 200 mM, due to protein aggregation through hydrophobic interactions. In contrast, at pH 7 and 10, solubility increased as NaCl was added up to 400 mM after which it remained constant. Changes in total SH content and Sowere highly related to the different molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Addition of NaCl had no effect on total SH content ( P > 0.05). This was in agreement with Thawornchinsombut and Park (2005) who reported that total SH content of alkali‐treated surimi of uncooked samples were not affected by addition of 10 to 400 mM NaCl.…”
Section: Resultssupporting
confidence: 93%
“…Addition of NaCl had no effect on total SH content ( P > 0.05). This was in agreement with Thawornchinsombut and Park (2005) who reported that total SH content of alkali‐treated surimi of uncooked samples were not affected by addition of 10 to 400 mM NaCl.…”
Section: Resultssupporting
confidence: 93%
“…Several studies have reported a similar phenomenon (Feng 2000; Mireles Dewitt et al. 2002; Thawornchinsombut and Park 2004).…”
Section: Resultsmentioning
confidence: 69%
“…This might have contributed more available hydrophobic patches on the protein molecules for the probe to bind. Moreover, the greater ability of PW muscle proteins to bind ANS at neutral and alkaline conditions could be promoted by salt ions (Thawornchinsombut and Park 2004, 2005). Electrostatic interactions possibly strengthen the hydrophobic interactions between ANS and proteins (Haskard and Li‐Chan 1998).…”
Section: Resultsmentioning
confidence: 99%
“…2000). Previous studies in our lab also demonstrated that pH and ionic strength play an important role on PW muscle proteins including protein solubility, biochemical properties and molecular distribution of proteins using sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) (Thawornchinsombut and Park 2004, 2005). However, few studies have employed both pH and ionic strength changes with the FPI prepared using the pH‐shift method.…”
Section: Introductionmentioning
confidence: 93%